Memorandum re Shortage of Nurses - Labour Party (Great Britain). National Executive Committee ; Labour Party (Great Britain). Advisory Committee on Public Health ; Joint Research Dept. of the Trades Union Congress and the Labour Party; MacCallum, Maude
1924-07 1924 1920s 8 pages - 2 - (92) they obtain from nurses during three years of training, refuse them certificates until they have given a fourth year's service, either by working in the hospital, or earning for it from three to four guineas a week as members of the private staff. (iii) That Hospital Authorities are not concerned with the proper education of probationers may be gathered from the fact that although the Nurses' Registration Act, 1919, specifically states that the nurses shall have a prescribed syllabus of training, in 1924 they are still without one. Those representing the working nurse fought strenuously for this syllabus on the first General Nursing Council for England and Wales, although there were only six of them to nineteen in the hospital interests. The Act has so far been contravened, in spite of the fact that at great expense (which the nurses have had to defray) and a vast amount of time and trouble, an excellent syllabus of training was drawn up and printed. Various employers realising that if this were to becone law, it would be necessary to provide proper teachers for probationers at extra expense to their hospitals, pressure was brought to bear, and the nineteen members representing the Hospital Authorities on the General Nursing Council have allowed the Act to be broken, as this compulsory syllabus has not yet been issued. (B) The attitude of the Hospitals towards nurses may be further surmised by the action of St. Thomas's Hospital Authorities in October 1922. In order to evade payment of unemployment insurance for their nurses, they forwarded to the Ministry of Labour a statement contending that staff nurses were domestic servants. This contention was only withdrawn when it was certain that the matter of Unemployment Insurance as far as nurses were concerned, would be 292/842/1/14